A randomized trial to study the comparative efficacy of phenylbutyrate and benzoate on nitrogen excretion and ureagenesis in healthy volunteers. (July 2018) - Nagamani, Sandesh C S; Agarwal, Umang; Tam, Allison; Azamian, Mahshid; McMeans, Ann; Didelija, Inka C; Mohammad, Mahmoud A; Marini, Juan C
Abstract Purpose Benzoate and phenylbutyrate are widely used in the treatment of urea cycle disorders, but detailed studies on pharmacokinetics and comparative efficacy on nitrogen excretion are lacking. Methods We conducted a randomized, three-arm, crossover trial in healthy volunteers to study pharmacokinetics and comparative efficacy of phenylbutyrate (NaPB; 7.15 gm−2 BSAday−1 ), benzoate (NaBz; 5.5 gm−2 BSAday−1 ), and a combination of two medications (MIX arm; 3.575 g NaPB and 2.75 g NaBzm−2 BSAday−1 ) on nitrogen excretion. Stable isotopes were used to study effects on urea production and dietary nitrogen disposal. Results The conjugation efficacy for both phenylbutyrate and benzoate was 65%; conjugation was superior at the lower dose used in the MIX arm. Whereas NaPB and MIX treatments were more effective at excreting nitrogen than NaBz, nitrogen excretion as a drug conjugate was similar between phenylbutyrate and MIX arms. Nitrogen excreted per USD was higher with combination therapy compared with NaPB. Conclusion Phenylbutyrate was more effective than benzoate at disposing nitrogen. Increasing phenylbutyrate dose may not result in higher nitrogen excretion due to decreased conjugation efficiency at higher doses. Combinatorial therapy with phenylbutyrate and benzoate has the potential to significantly decrease treatment cost without compromising the nitrogen disposal efficacy.